Nursing management for 5 patients undergoing Rituximab treatment for cryoglobulinemia-associated membranoproliferative glomerulonephritis (利妥昔单抗治疗5例冷球蛋白血症相关膜增生性肾小球肾炎患者的护理) - LI Aijuan (李爱娟) (中西医结合护理)
This paper reviewed the clinical data of 5 patients with cryoglobulinemia-associated membranoproliferative glomerulonephritis(MPGN), and summarized the Rituximab treatment (RTX) paln, medication care and nursing process. A single dose of rituximab was effective to reduce the level of cryoglobulin and stabilize kidney function of patients. Comprehensive nursing interventions included strictly fluid and volume management by daily weighing and intake and output volume recording, regulation of the medication care process, development of emergency risk plans for specialist treatment and emergency kit preparation, psychological care, peer education and creating an optimal sleep environment. (本文回顾5例冷球蛋白血症相关膜增生性肾小球肾炎(MPGN)患者的临床资料, 总结利妥昔单抗(RTX) 治疗方案及用药护理过程。单次足量RTX可以有效降低冷球蛋白血症相关MPGN患者的冷球蛋白水平, 稳定肾功能。护理干预措施包括运用每日称重及出入量记录法严格进行容量管理; 规范用药护理流程, 制定专科治疗应急风险预案并完善应急包配备; 开展针对性的心理护理, 适时开展同伴教育, 为患者营造良好的睡眠环境。)